Aldehyde-substituted acceptor-DTE-acceptor-type dithienylethene as a versatile building block for near-infrared photochromic materials. Issue 1 (January 2020) - Wang, Yangyang; Qin, Ming; Song, Yufei; Pei, Yingying; Dai, Yijie; Ma, Yongjie; Li, Ziyong
A novel aldehyde-substituted acceptor-DTE-acceptor-type dithienylethene derivative, in which the difluoroboron β-diketonate and aldehyde groups at the termini of the dithienylethene function as electron acceptors, has been developed. The structure was confirmed by 1 H NMR, 13 C NMR, 19 F NMR, high-resolution mass spectrometry (electrospray ionization) and infrared. The derivative displays solvent-dependent photophysical properties, visible light–triggered near-infrared photochromism, and fluorescent switching behavior in solvents of different polarity. Moreover, it can be utilized as a versatile building block to construct novel near-infrared photochromic materials.